A Flexible Hexacarboxylate-Samarium(III) Metal-Organic Framework: Synthesis, Structure and Spectroscopic Properties - Sireenart Surinwong (2018)
A new flexible triazine-based polycarboxylate metal-organic framework, [Sm2(TTHA)(H2O)4]·9H2O (I) (TTHA = 1,3,5-triazine-2,4,6-triamine hexaacetate), has been synthesized under hydrothermal conditions and characterized by single crystal X-ray diffraction, elemental analysis and FT-IR spectroscopy. Crystal data for I are monoclinic C2/c, a = 12.6974(13) Å, b = 16.7309(12) Å, c = 14.8076(15) Å, β = 91.452(8)°, V = 3,144.7(5) Å3. Each SmIIIion is 9-coordinate in a distorted tri-capped trigonal prismatic geometry; but, the principal inorganic building block is Sm2O16, which comprises two of these polyhedra that share an edge. The complex exhibits a three-dimensional open-framework structure of approximately 31 % void volume, which comprises two types of channels oriented in three directions; [0 0 1], [1 1 0] and [-1 1 0]. The network can be simplified into either the cooperite (pts) or anatase (ant) topologies depending on the choice of nodes. The UV-Vis spectra of the compound are dominated by the absorption of the TTHA ligand. Thermogravimetric analysis shows that the loss of channel and coordinated water upon heating occurs in two distinct steps. © 2013 Springer Science+Business Media New York.